Comparison of Shaping Ability of Different Single-File Systems Using Microcomputed Tomography - Elashiry, Mohamed Mohamed; Saber, Shehab Eldin; Elashry, Salma Hasan (European Journal of Dentistry, 2020)
Objectives To evaluate the shaping ability of four different single-file systems using micro-computed tomography (micro-CT).Materials and Methods Eighty mesiobuccal and mesiolingual canals of permanent mandibular molars were randomly assigned to four groups according to the file used; WaveOne Gold, RECIPROC Blue, HyFlex EDM, and One Shape (n = 20). The samples were scanned using micro-CT for the preinstrumentation record; then the canals were instrumented and scanned for the postinstrumentation records.Statistical Analysis The data were then analyzed statistically using one-way analysis of variance (ANOVA) with the level of significance set at α = 0.05.Results The results of canal centering ratio and canal transportation showed that no significant difference was found among the four file groups at the middle and the coronal levels. However, a significant difference was found at the apical level (p < 0.05), where WaveOne Gold showed the best centering ratio and the least amount of canal transportation. The change in the canal volume was significant at the coronal level (p < 0.05), whereas the change in the canal volume was higher for the HyFlex EDM group than the other groups. No significant difference was found between the other groups at the apical level, middle level, or in the total percentage of canal volume.Conclusion WaveOne Gold produced a more centralized canal preparation with a lesser amount of transportation at the apical level. HyFlex EDM showed the highest canal volumetric change at the coronal level. The interim design of the endodontic files has a high impact on the behavior of the file inside the root canal.
Keywords: canal centering; canal volumetric change; microcomputed tomography; single file; transportation